Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-77 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Exercising on the special CDT device with coordinated support by the Author. The Author recognized with the left hand when Nefeli started to sweat in the leg first time after the SCI, which means that the sympathetic nervous system re-innervated the body below the injury level Th10.